Pengaruh Earning Per Share Dan Price To Earning Ratio Terhadap Harga Saham Yang Terdaftar Di Indeks Kompas100 Periode 2021-2024 - Eric Arianto; Faradila Meirisa (Universitas Multi Data Palembang, 2026)
This study aims to examine the influence of Earning Per Share (EPS) and Price to Earning Ratio (PER) on Stock Prices of companies listed in the KOMPAS100 index on the Indonesia Stock Exchange for the 2021-2024 period, both partially and simultaneously. The type of research used is a quantitative approach with an associative method. The sampling technique used purposive sampling, resulting in 62 sample companies with a total of 248 observation data. The data analysis technique used is multiple linear regression analysis supported by SPSS 26 software. The partial results of this study indicate that the EPS variable has a positive and significant influence on Stock Prices with a t-value of 12.798 > t-table 1.651. Similarly, the PER variable has a positive and significant influence on Stock Prices with a t-value of 4.769 > t-table 1.651. Simultaneously, the F-test results show that both EPS and PER variables together have a significant influence on Stock Prices with an F-value of 35.930 and a significance value of 0.000. The coefficient of determination (Adjusted R Square) indicates that stock price variations are influenced by these two variables by 41.9%, while the remaining 58.1% is explained by other factors outside this research model.